Kamdeva on mancha - Temples of India Project Team (Jio Institute, 2024)
Couples invoking shringara rasa (associated with romance, love, and attractiveness between lovers) are framed in panels with pillars and tiered shikhara with gavashka (horseshoe) motifs. The central figures are wearing heavy jewellery, elaborate headgear, and garments, indicating they are a royal couple. The central male figure is seated on a circular raised seat in a lalitasana pose, firing an arrow from a bow. Standing on his left are two female figures (faces defaced), looking towards him. The female on his immediate left is holding a flower in her right hand. The female to his far left is holding a floral scroll. The female figure on his right is damaged. A bunch of mangoes hang above them. As mangoes are symbols of kama or sexual desire, this may be a depiction of Kamadeva (Hindu God of erotic love, pleasure, and desire) and the females may be apsaras (celestial nymphs) or his consort, Goddess Rati.